Diseño e implementación de un sistema desktop para la administración y gestión eclesiástica, aplicando la metodología crystal para la parroquia San Buenaventura ubicada en la ciudad de Latacunga provincia de Cotopaxi en el periodo 2013 - Chillagana Salazar, Cándida Paula (2015)
This study describes the design and implementation of a desktop system for the ecclesiastical administration and management at the Parish Church of San Buenaventura, this system is a software tool which allows you to manage existing files about people who have done different sacraments in this church. This software performs general and specific queries generating reports of all people who are registered in it. Also, it allows only generation of Baptism and Marriage certificates according to user´s requirement. For the development of this software was wed Visual Basic.net was used as the programming language, MySQL as database, as well as Crystal Clear is also used, as a development methodology of agile software which allows you to interact directly with the Sponsor (Owner or sponsor system)....